Cellulose template-based triboelectric nanogenerators for self-powered sensing at high humidity. (April 2023) - Zhang, Wanglin; Chen, Xianghui; Zhao, Jiamin; Wang, Xinyue; Li, Xiuzhen; Liu, Tao; Luo, Bin; Qin, Ying; Zhang, Song; Chi, Mingchao; Wang, Shuangfei; Nie, Shuangxi
Abstract: Triboelectric nanogenerators (TENGs) have ideal applications in the field of self-powered sensing thanks to their simple structure and flexible working mode. However, the weak operating properties of triboelectric materials in high humidity environments limit the wide application of TENG as sensors. To solve this problem, this work prepared hydrophilic triboelectric materials with natural cellulose as the template and used them for self-powered sensing in high humidity environments. Thanks to the interconnected network of the cellulose scaffold, the complex morphology of the material constructed in concert with Ti3 C2 Tx during templating provides abundant adsorption sites for water molecules. Over a broad humidity range (40%−90% relative humidity (RH)), the moisture-sensitive triboelectric material can sustain outstanding performance in 150 s with high sensitivity (0.8/1%). The cellulose template-based triboelectric material transmits electrical signals to the user interface wirelessly, enabling self-powered sensing in high humidity environments. This study provides a novel strategy for the design and preparation of high-performance triboelectric materials using cellulose as a template and promotes the study of self-powered sensing in high humidity environments. Graphical Abstract: ga1 Highlights: Preparation of a cellulose template-based triboelectric material for high humidity. The material has high sensitivity and high stability over a wide humidity range. The material enables humidity sensing and respiration monitoring in high humidity.